Exclusive cow’s milk intake and asymptomatic anaemia (Indian Journal of Case Reports, 2019)
It is a strong tradition to introduce cow’s milk (CM) early in infancy. There are reports of various deleterious health effects of CM in infancy. We describe an asymptomatic, well-thriving infant who was exclusively fed with CM and had severe iron deficiency anemia. An eleven-months-old infant during the consultation for fever was found to have severe pallor. Except for systolic murmur, she had a normal systemic examination. Hemoglobin was 2.2 gm/dl, her RBC count, volume and hemoglobin concentration were low. Iron studies done showed a severe iron deficiency state. She was given packed cell transfusions; iron supplements were initiated. Introduction of complementary foods rich in iron is imperative as iron stores begin to deplete at four to six months of age. Initiation of CM early in infant feeding can lead to very severe anemia which can be mitigated by CM fortification, iron supplementation in infants.